The border concept and the european union: the case of schengen regime with special reference to Turkey - Keskin, Özge (My University, 2011)
Bu tez sınır kavramı üzerinde özellikle Avrupa’ya ilişkin kuramsal bir çerçeve geliştirerek, kavramın gelişimini incelemektedir. Aynı zamanda, Avrupa’nın sınır anlayışını sınır kavramının çeşitli tanımları ve türlerinden yola çıkarak irdelemektedir. Schengen rejimi söz edilen sınır anlayışını daha geniş bir çerçevede analiz etmek amacıyla bu tezin örnek çalışmasını oluşturmaktadır. Tez, Avrupa sınır yönetiminin dönüşümüyle ilgili temel ayrıntılara Türkiye'ye referans vererek değinmektedir. Bu anlamda, çalışma iki ana eksenden oluşmaktadır. Bunlardan birincisini, Avrupa Birliği sınırlarının dinamiklerinin incelenmesi; ikincisini de sınır politikaları konusundaki Türkiye ile Avrupa Birliği arasındaki müzakereler dahil olmak üzere her iki tarafın uygulanmalarının gözlemlenmesinden yola çıkarak Schengenleşme/ Schengenleştirme sürecinin analiz edilmesi oluşturmaktadır.

This thesis aims to develop a theoretical framework on the border concept regarding Europe and examines the evolution of the concept. It also explores related aspects of the border concept including their definitions and types. The European understanding of border investigated through (non) networked border, march, colonial frontier and limes. This understanding is analysed within a broader framework of the Schengen regime as the case study. The thesis elaborates how the European border management evolved by putting a special reference to Turkey. In this manner, the main axes of this study constitute first, evaluating the change in the understanding of the borders of the European Union, and then analyzing the Schengenization process by analyzing the implementations of the border policies of the European Union and Turkey including the negotiation process.
Keywords: Avrupa Birliği; Avrupa Birliği_Türkiye; Dış İlişkiler; Uluslararası İlişkiler